ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI USAHATANI JAGUNG DI DESA UELENE KECAMATAN PAMONA SELATAN KABUPATEN POSO - Montjou, Rivaldy Yahya; Christoporus, Christoporus; Sirappa, Erny (Fakultas Pertanian, Universitas Tadulako, 2024)
This study examined the effect of various production factors—including land area, seed type, urea fertilizer application, labor input, and farmer age—on corn production in Uelene Village. Respondents were selected via a simple random sampling method from a population of 102 farmers, resulting in a sample size of 31 farmers. The analysis employed the Cobb-Douglas production function to evaluate the relationships between the variables. The findings indicate that 97.2% of the variance in corn production can be attributed to the specified variables, while the remaining 2.8% is accounted for by other factors not included in the model. The F-value obtained (F-count = 171.015) exceeds the critical value (F-table = 2.60), suggesting a significant simultaneously effect of the production factors on corn production in Uelene Village. In terms of individual contributions, three variables—land area, seed type, and urea fertilizer—demonstrated a significant effect on corn production, implying that increases in these factors correspond to higher yields. Conversely, labor input and farmer age were found to have no significant effect on corn production in this context. This research contributes valuable insights for agricultural stakeholders in optimizing resource allocation for enhanced corn production in the region.